K2-HERMES II. Planet-candidate properties from K2 Campaigns 1-13. Issue 1 (3rd June 2020) - Wittenmyer, Robert A; Clark, Jake T; Sharma, Sanjib; Stello, Dennis; Horner, Jonathan; Kane, Stephen R; Stevens, Catherine P; Wright, Duncan J; Spina, Lorenzo; Čotar, Klemen; Asplund, Martin; Bland-Hawthorn, Joss; et al.
ABSTRACT: Accurate and precise radius estimates of transiting exoplanets are critical for understanding their compositions and formation mechanisms. To know the planet, we must know the host star in as much detail as possible. We present complete results for planet-candidate hosts from the K2-HERMES survey, which uses the HERMES multi-object spectrograph on the Anglo-Australian Telescope to obtain $R\sim 28\, 000$ spectra for more than 30 000 K2 stars. We present complete host-star parameters and planet-candidate radii for 224 K2 candidate planets from C1–C13. Our results cast severe doubt on 30 K2 candidates, as we derive unphysically large radii, larger than 2 R Jup . This work highlights the importance of obtaining accurate, precise, and self-consistent stellar parameters for ongoing large planet search programs – something that will only become more important in the coming years, as TESS begins to deliver its own harvest of exoplanets.